2007
DOI: 10.2519/jospt.2007.2412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Voltage Microamperage Stimulation on Tendon Healing in Rats

Abstract: a chilles tendon ruptures are common in athletes and the middle-aged, and there have been increasing reports of Achilles tendon ruptures in recent decades. 25,28 Despite the intrinsic capacity of spontaneous recovery in injured tendons, 26,27 the process often takes a long time and the qualities of the repaired tendons are inferior to those of intact tendons. 16,20,19,31,32 To restore the optimal function of injured tendons it is important to develop therapeutic interventions that facilitate the process of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Electric stimulation with a frequency of 10 Hz, albeit without explaining the details of the current, showed greater maximum tension in rat tendons. This study did not take into account the cross section of the tendon 40 . Nevertheless, a study of rats electrically stimulated at a low frequency (10 Hz) and with a positive (anodic) polarized current confirmed the increased maximum tension of the tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Electric stimulation with a frequency of 10 Hz, albeit without explaining the details of the current, showed greater maximum tension in rat tendons. This study did not take into account the cross section of the tendon 40 . Nevertheless, a study of rats electrically stimulated at a low frequency (10 Hz) and with a positive (anodic) polarized current confirmed the increased maximum tension of the tendons.…”
Section: Discussionmentioning
confidence: 99%
“…The time and frequency of HVPC application are important factors in the healing process. Other studies were found in the literature that obtained satisfactory results with an electrical current for tendon healing, but the evaluations were made 14 days after the injury 23 , 24 . However, there are studies that used low level laser therapy (LLLT) on tendons submitted to partial rupture of the Achilles tendon in rats using the same lesion model as this study, and they observed an increase in collagen realignment 8 , 9 , 11 and type I collagen percentage after 5 days of treatment 8 , 11 and increase of blood vessel numbers after 3 and 5 treatment days 10 .…”
Section: Discussionmentioning
confidence: 99%
“…There are other important results using different types of current for electrical stimulation, such as enhancement of intrinsic tenoblastic repair in vitro 29 and increase in capillaries and fibroblasts at the early stage of tissue repair 23 ; in terms of low voltage microamperage stimulation, an improved tensile strength of partially transected Achilles tendons at four weeks after injury 24 and burst transcutaneous electrical nerve stimulation (TENS) that inhibited collagen I and III production and impaired its alignment during healing of partial rupture of the Achilles tendon in rats 30 . More studies should be conducted with different parameters, e.g., analysis of collagen synthesis using real-time polymerase chain reaction (RT-PCR) or immunohistochemistry, identifying some key genes and proteins important for healing tendon such as vascular endothelial growth factor (VEGF), transforming growth factor-β (TGF-β), insulin-like growth factor (IGF), connective tissue growth factor (CTGF), matrix metalloproteinases (MMPs), tenascin C, and important proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The electrotherapeutic effects of the microcurrent, which presents low cost and an easier application, 21 trigger a series of events, among which we can mention the increase of cellular metabolism, local pH normalization, fibroblast proliferation, tissue contractility actions, increased protein synthesis, increased permeability of cell membranes, and tissue bioelectricity normalization. 20,21 Chan et al 22 demonstrated that the application of the microcurrent in the Achilles tendon of rats 4 weeks after the injury, increased its mechanical resistance. Ahmed et al 23 used the microcurrent in the Achilles tendon of rabbits on the 3rd, 5th, and 8th weeks after the injury and concluded that the electrical stimuli reduced the inflammation and promoted the reorganization of the collagen fibers.…”
Section: Introductionmentioning
confidence: 99%